Підвищення рівня технічної підготовки дзюдоїстів на етапі перед змагальної підготовки - Кадіров, Кадір Беюк Ага Огли; Kadirov, Kadir Beyuk Aha Ohly (Ірпінь, 2024)
У кваліфікаційній роботі розглядаються питання підвищення рівня технічної підготовки дзюдоїстів на етапі підготовки до змагальної діяльності. Проаналізовано й узагальнено оптимальне поєднанню різних форм, методів та засобів спортивного тренування дзюдоїстів, що дає змогу найефективніше розв’язувати завдання підготовки спортсменів до змагань. Для успішної змагальної діяльності необхідний постійний методичний пошук нових резервів як в окремих видах підготовки дзюдоїстів, так і в усій системі підготовки в цілому, який повинен базуватися на швидкому реагуванні на вимоги спортивної практики до підготовленості спортсменів.

Тhe qualification work considers the issues of increasing the level of technical training of judokas at the stage of preparation for competitive activities. The optimal combination of various forms, methods and means of sports training of judokas is analyzed and generalized, which makes it possible to most effectively solve the problems of preparing athletes for competitions. For successful competitive activity, it is necessary to constantly search for new reserves both in individual types of training of judokas and in the entire training system as a whole, which should be based on a rapid response to the requirements of sports practice for the preparedness of athletes.
Increasing the level of technical training of judokas at the stage of pre-competitive training
Keywords: дзюдо; тренувальний процес; спорт; змагання; підготовленість; judo; training process; sport; competition; preparedness